Two new polystomes (Monogenea: Polystomatidae) from the eyes of North American freshwater turtles - Preez, Louis H. Du; Morrison, Christa (Zootaxa, 2012)
Neopolystoma moleri n. sp. and Neopolystoma grossi n. sp. are described as new polystome species on the eyes of Apaloneferox and Pseudemys concinna floridana, respectively from Florida, USA. Eleven other polystome species are currently knownfrom chelonian hosts in the USA, but only Neopolystoma elizabethae and Neopolystoma fentoni were described from the eye.Ocular polystomes are characterized as having spindle-shaped eggs; an exceptionally firm grip on the host; as well as the abilityto stretch, which gives them the advantage of being stationary while extending to feed, reducing the risk of being dislodged.The two new species can be distinguished from known Neopolystoma species by a combination of characteristics including marginal hooklet morphology.